Complex Posthuman Relations : Ideological Contradiction in Kazuo Ishiguro’s Klara and the Sun through the Paradigm of Marxism - Rossi, Paavo (My University, 2024)
In this thesis I investigate ideological contradiction in Kazuo Ishiguro’s 2021 novel Klara and the Sun. I analyze ideological contradiction in the characterization of the protagonist, Klara, within three themes: cognitive autonomy, intrinsic value, and post-humanity. I also investigate how ideological contradiction diminishes the novel’s critique of capitalism and anthropocentrism. The theoretical framework of this thesis is Marxist. I utilize Marxist theories and concepts, such as the alienation theory, to study capitalist ideologies within the text. To further analyze the emergence of ideological contradiction, I utilize Gramsci’s theories on hegemony and counter-hegemony, and Althusser’s theories on ideology and interpellation. As per my analysis, Klara’s cognitive autonomy is limited but not entirely heterogeneous. Her coding encourages capitalist and anthropocentric ideologies, which she is unable to critically examine. Klara can, however, resist her teachings occasionally. Klara’s internal value is often diminished by the society, but as she forms interpersonal relationships, she is granted some agency and worthiness by the people closest to her. Klara has some unique skills and features which highlight her posthuman uncanny, but her empathy and kindness are used to challenge the ideals of human superiority and perfectibility. The novel, however, fails to thoroughly challenge the status quo ontology of the identities of the human and posthuman. I encourage further readings of the novel to better understand our relationship with the posthuman. Feminist and ecological readings can further reveal more about the aspects of nature and gender within technological Otherness. I also advocate for Marxist readings to deconstruct the naturalizing effects of capitalism.
Keywords: Marxist literary criticism, Marxism, ideology, ideological contradiction, posthumanism, capitalism, Kazuo Ishiguro